Local Economic Development Through the Nature Tourism Sector Climbing Mount Marapi in Nagari Aie Angek X Koto Tanah Datar District (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study is to determine the implementation of local economic development contained in natural tourism climbing Mount Merapi in Nagari Aie Angek, X Koto District, Kabupataen, Tanah Datar. Local economic development (PEL) through natural tourism Climbing Mount Merapi in Nagari Aie Angek has been going well and running with existing rules. High community participation is the key to the survival of tourism and also the economic improvement of the surrounding community. The results showed that local economic development in Nagari Aie Angek has fulfilled six aspects contained in the first PEL target group. The PEL target group in developing the local economy of the Nagari Aie Angek area involves local communities, Second, the factor of Mount Merapi climbing tourism location has been well developed by connecting the main road with easily accessible tourist sites, Third, the synergy of Mount Merapi climbing tourism is an alternative to achieve the welfare of its community. Fourth, sustainable development where the development of natural tourism is the main long-term to improve community welfare. Fifth, partnerships with local governments and BKSDA with the community, Sixth, the management of the natural tourism sector of Mount Merapi Climbing is carried out in a mutual cooperation manner by involving all community stakeholders, traditional leaders and the Nagari government.